The Relationship Between Sedentary Lifestyle and Body Mass Index Among Junior High School Students at Jayapura Christian School - Pardamean, Engelberta; Wonda, Elvira; Sungono, Veli (Medicinus, 2022)
Introduction: As a result of today's technology advancements, many people, including youngsters, are spending more time watching television, playing video games, or using social media on computers or phones. Sedentary lifestyle refers to behaviors like these. Students' activities became passive as a result of studying online at home. As a result, the chance of acquiring more weight and eventually being obese increases. That is the basic issue addressed in the study. The majority of youngsters spend their time on video games, television, or social networking. One of the signs of a sedentary lifestyle is a lack of physical activity. In youngsters, a lack of physical activity might raise the chance of being overweight or obese.Objective: The purpose of this study is to look into the link between a sedentary lifestyle and a high BMI among Jayapura Christian School Junior High School students.Methods: This is a cross-sectional study including Jayapura Christian School Junior High School students. Purposive sampling is a strategy for collecting data. The Adolescent Sedentary Activity Questionnaire (ASAQ) was used to collect data and determine Sedentary Lifestyle. In addition, BMI categories were utilized to determine whether someone was normal, overweight, or obese.Results: The majority of the respondents have an overweight or obese BMI (n=35; 67.3 percent) and a normal BMI (n=17; 32.7 percent), as well as a heavy sedentary lifestyle (n=45; 86.5 percent) and a moderate or light (n=7; 13.5 percent) lifestyle. Using the chi-square statistical test, the results of the two variables analysis, sedentary lifestyle and body mass index category, yielded a p-value of 0.003 and an odds ratio of 17.37 (95 percent CI:2.262-440.1). When compared to students who have a mild or moderate sedentary lifestyle, students with a severe sedentary lifestyle have odds 17.37 times higher chance of having a BMI above normal.Conclusions: There is a substantial link between a sedentary lifestyle and a BMI over the usual limit among Jayapura Christian School Junior High School students.